A Jak1/2 inhibitor, baricitinib, inhibits osteoclastogenesis by suppressing RANKL expression in osteoblasts in vitro - Murakami, Kohei; Kobayashi, Yasuhiro; Uehara, Shunsuke; Suzuki, Takako; Koide, Masanori; Yamashita, Teruhito; Nakamura, Midori; Takahashi, Naoyuki; Kato, Hiroyuki; Udagawa, Nobuyuki; Nakamura, Yukio (PLOS ONE, 2017)
The Janus kinases (Jaks) are hubs in the signaling process of more than 50 cytokine or hormone receptors. However, the function of Jak in bone metabolism remains to be elucidated. Here, we showed that the inhibition of Jak1 and/or Jak2 in osteoblast-lineage cells led to impaired osteoclastogenesis due to the reduced expression of receptor activator of nuclear factor-κB ligand (RANKL). Murine calvaria-derived osteoblasts induced differentiation of bone marrow cells into osteoclasts in the presence of 1,25-dihydroxyvitamin D3 (1,25D3) and prostaglandin E2 (PGE2) in vitro. However, treatment with the Jak1/2 inhibitor, baricitinib, markedly inhibited osteoclastogenesis in the co-culture. On the other hand, baricitinib did not inhibit RANKL-induced osteoclast differentiation of bone marrow macrophages. These results indicated that baricitinib acted on osteoblasts, but not on bone marrow macrophages. Baricitinib suppressed 1,25D3 and PGE2-induced up-regulation of RANKL in osteoblasts, but not macrophage colony-stimulating factor expression. Moreover, the addition of recombinant RANKL to co-cultures completely rescued baricitinib-induced impairment of osteoclastogenesis. shRNA-mediated knockdown of Jak1 or Jak2 also suppressed RANKL expression in osteoblasts and inhibited osteoclastogenesis. Finally, cytokine array revealed that 1,25D3 and PGE2 stimulated secretion of interleukin-6 (IL-6), IL-11, and leukemia inhibitory factor in the co-culture. Hence, Jak1 and Jak2 represent novel therapeutic targets for osteoporosis as well as inflammatory bone diseases including rheumatoid arthritis.